Power generation by ocean waves : production of an ocean wave generator - Lim, Jacob Fang Yao. (2013)
This report presents the detailed process of producing and testing an ocean wave generator. The wave generator is to be used in a laboratory to recreate an ocean wave environment, which will be used in a separate project that deals with the production of a “ocean wave energy - to electricity” harnessing machine.